Modul E-Learning Sebagai Penunjang Pembelajaran Pada Siswa SMK N 4 Rambah Kelas XI Jurusan TKJ - Wati, Rina; Setiawan, Agung (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2023)
The problem in this research is that the learning carried out is still conventional, so it does not support this learning. The aim of this research is to look at e-learning modules as supporting learning at SMKN 4 Rambah. This research uses research and development methods. The sample in this research was students of SMKN 4 Rambah Class XI TKJ Department. The data collection technique in this research is using questionnaires. The results of the answers to the questionnaire above, from 30 people with a total of 45 questions answered, of which one question has a value of 1 if the answer is yes and 0 if the answer is no, from these results we get an interval class of 20 – 24 with 3 people or 10%, 25 – 29 with 5 people or 17%, 30 – 34 with 15 people or 50%, 35 – 39 with 4 people or 13%, 40 – 44 with 3 people or 10%. The conclusion in this research is that students of SMKN 4 Rambah class. Kata Kunci: Modul E-Learning, Penunjang Pembelajaran,Siswa Kelas XI TKJ